(untitled) (Global Journals of Research in Engineering, 2012)
The use of static analysis and in situ methods were adopted to evaluate the capacity of piles innon cohesive soils of a typical sedimentary formation The piles were for a proposed five span five span bridge along road dualisation project traversing Northwestern and Northeastern Nigeria The results shows that the bearing capacity of piles were higher by the static method than those evaluated by in situ techniques Specifically the capacity of piles ranges from 2829 12 147 kN and 2454 6009 kN for static analysis and in situ method respectively The latter method has proved to be more reliable and shows more inherent agreement than the static method